Penerapan aspek-aspek disiplin dalam manajemen bisnis syariah Terhadap Sharia business performance (Studi Pada Pondok Pesantren Riyadlul Jannah Pacet Mojokerto dan Unit usaha yang dikembangkan) - Mamang Hariyanto (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2020)
The purpose of this research is to analyze and explain the effect of state of mind - mental attitude, system of rules of conduct and system of set norms - criteria and standards simultaneously and partially on Sharia business performance. This type of research is explanatory research. The results of hypothesis testing show that there is a simultaneous and partial significant effect of state of mind - mental attitude (X1), system of rules of conduct (X2) and system of set norms - criteria and standards (X3) on Sharia business performance (Y) .